Rare and Underestimated Association of Pulmonary Embolism and Olanzapine Therapy; Report of Two Cases - Rasras, Hammam (Arch Acad Emerg Med, 2021)
Venous thromboembolic disease (VTD) is a very common and severe pathological condition in which there are many predisposing factors. Olanzapine is a drug frequently used in psychiatric practises; it is thought to increase the risk of VTD. Here, we report two cases, a young man and a woman, with a medical history of schizophrenia treated by olanzapine who developed pulmonary embolism and we did not find any aetiologies of VTD in them. Due to the link between olanzapine and pulmonary embolism, which has been previously described, olanzapine is considered responsible for this problem. Two mechanisms have been reported in the literature in this regard; significant weight gain and lethargy, which are very common side effects of olanzapine. So far, no direct effect of olanzapine on platelet aggregation or coagulation has been found. In patients developing VTD while being treated with olanzapine, discontinuation of olanzapine as a treatment option must be done with an adjustment of antipsychotic treatment and regular monitoring of psychic symptoms. Since the diagnosis of pulmonary embolism is not easy to make in a schizophrenic patient, clinicians should take that in consideration when prescribing these drugs and when facing clinical situations where VTD is suspected.